Strategi Pemeliharaan Berbasis CBM+ pada Mesin TPE331 untuk Meningkatkan Keandalan Operasional: Studi Kasus Pesawat CASA 212-200 di PT NTP - Ramadhani, Agita; Amperiawan, Gita; Manawan, Maykel; Gani, Erzi Agson; Furqon, M Zainal (Jurnal Ilmiah Teknologi dan Rekayasa, 2025)
Aircraft engine maintenance strategies have evolved from schedule-based approaches toward condition-driven systems that emphasize actual component health conditions. The TPE331 turboprop engine used on the CASA 212-200 aircraft is critical in supporting both military and civil aviation operations. However, its maintenance process faces challenges related to high operational intensity, diverse operating environments, spare part availability, and turnaround time. This research was conducted at PT Nusantara Turbin dan Propulsi (NTP) to analyze the existing maintenance system and to propose the implementation of Condition-Based Maintenance Plus (CBM+) as an optimization strategy. The research employed a qualitative descriptive approach using maintenance records, engine performance parameters, and operational cost data. The results show that CBM+ implementation has the potential to reduce unexpected downtime, improve cost efficiency by approximately 8–12%, and enhance fleet readiness through early detection of component degradation. This research demonstrates that CBM+ provides not only technical benefits but also strategic value in supporting the transformation of the national MRO industry toward data-driven maintenance practices.